Optimizing Social Media as an Innovation in Islamic Religious Education Learning - Siregar, Surianti; Nuddin, Muhammad (Fahmina: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the optimization of social media as an innovation in PAI learning and identify the opportunities and challenges that accompany it. The research method used is a qualitative approach with the type of literature study, by analyzing various academic literature, previous research results, and relevant educational policies. The results of the study show that the use of social media in PAI learning is able to increase interest in learning, expand access to Islamic learning resources, and encourage interaction and active participation of students. However, social media optimization also faces serious challenges, such as the potential spread of unverified religious content, low digital literacy, and the risk of degradation of ethical and spiritual values. Therefore, this study emphasizes the importance of the role of educators in directing the wise and educational use of social media, as well as the need to strengthen digital literacy and media ethics based on Islamic values.